2004
DOI: 10.1016/j.clpt.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibition and smoking potentiate the kinin response to cardiopulmonary bypass

Abstract: Preoperative ACE inhibitors and smoking potentiate the kinin response to CPB and may contribute to the hemodynamic and fibrinolytic response observed during CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…[1, 31, 47] Prior studies have indicated that ACE inhibition enhances the bradykinin response during CPB. [48] Moreover, bradykinin increases oxidative stress and worsens ischemia/reperfusion renal injury in an animal model. [49] Thus, ACE inhibition, through an increase in bradykinin concentrations, could increase oxidative stress and contribute to AKI.…”
Section: Discussionmentioning
confidence: 99%
“…[1, 31, 47] Prior studies have indicated that ACE inhibition enhances the bradykinin response during CPB. [48] Moreover, bradykinin increases oxidative stress and worsens ischemia/reperfusion renal injury in an animal model. [49] Thus, ACE inhibition, through an increase in bradykinin concentrations, could increase oxidative stress and contribute to AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of BK1-5 achieved during intra-arterial administration that resulted in maximal platelet inhibition was approximately 50-to 75-fold higher than physiological concentrations Pretorius et al, 2004) but 150,000-fold lower than the concentrations required to inhibit platelet aggregation or in vitro (Hasan et al, 1996(Hasan et al, , 1999 or in vivo in dogs. Species differences may account for the difference in the potency of BK1-5 in dogs and humans.…”
mentioning
confidence: 99%
“…Whether or not bradykinin produces detrimental effects may depend on the underlying activity of the kallikrein–kinin system. During CPB, the kallikrein–kinin system is activated 6 , 7 and increased bradykinin may cause detrimental effects such as enhanced stimulation of t‐PA release, with resulting fibrinolysis and bleeding. The endothelium is the principal site of t‐PA synthesis and storage, whereas PAI‐1 is synthesized and secreted from several sources including endothelium, adipose tissue, liver, and platelets 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin, acting through its B 2 receptor, stimulates the release of nitric oxide, inflammatory cytokines, and tissue‐type plasminogen activator (t‐PA) 9 , 10 , 11 , 12 , 13 , 14 . Specifically, we have found that during CPB, bradykinin concentrations correlate inversely with mean arterial pressure (MAP) and directly with t‐PA 6 . Studies in animals suggest that bradykinin B 2 receptor antagonism inhibits reperfusion‐induced increases in vascular permeability and neutrophil recruitment 15 , 16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation